Overhydration prevalence in peritoneal dialysis - A 2 year longitudinal analysis - Aguiar, P. (2016)
Hypervolemia is a major concern in dialysis patients, and is associated with increased cardiovascular risk and death. Cross sectional analysis have previously demonstrated that peritoneal dialysis (PD) patients are not more overhydrated when compared to haemodialysiś ones. This study was designed to evaluate longitudinal trends in hydration status and corporal composition in a PD population.